2009
DOI: 10.1590/s0044-59672009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Indução de metabólitos secundários em plântulas de Hypericum brasiliense Choisy crescendo in vitro

Abstract: A produção de rutina, quercetina, 1,5-diidroxixantona e ácido betulínico foi investigada em plântulas de H. brasiliense crescendo in vitro, sob a influência de ácido salicílico, polietilenoglicol, NaCl, 24-epibrassinolídeo, benzotiadiazole (BION), metiljasmonato e concentrações aumentadas de boro e nitrogênio no meio líquido de cultura. As avaliações foram feitas após 5 e 10 dias do início dos tratamentos. Os maiores aumentos de conteúdo foram observados com quercetina para boro e ácido salicílico aos 5 dias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…Even though Velloso et al (2009), andCroteau et al (2000) reported that biotic and abiotic factors, such as hormones, light, lack of nutrient, and water stress may promote an increase in total phenolic levels, this study did not show effect on total phenolic levels of gherkin with increasing levels of salinity up to 5.0 dS m -1…”
Section: Quality At Harvestcontrasting
confidence: 76%
“…Even though Velloso et al (2009), andCroteau et al (2000) reported that biotic and abiotic factors, such as hormones, light, lack of nutrient, and water stress may promote an increase in total phenolic levels, this study did not show effect on total phenolic levels of gherkin with increasing levels of salinity up to 5.0 dS m -1…”
Section: Quality At Harvestcontrasting
confidence: 76%
“…Increase of hypericin and betulinic acid levels upon Hypericum brasiliense Choisy exposure to drought represents an antioxidant response to ROS production [57,58]. Artemisia annua plants tolerate well water deficit treatments showing increased accumulation of artemisinin, a potent anti-parasitic drug, as proved in greenhouse experiments.…”
Section: Protective Role Of Secondary Metabolites In the Plant Responmentioning
confidence: 94%